2019
DOI: 10.1371/journal.pone.0225195
|View full text |Cite
|
Sign up to set email alerts
|

From social interactions to interpersonal relationships: Influences on ultra-runners’ race experience

Abstract: ObjectivesUltra-running’s psychological and physiological dimensions have been widely studied. However, the social dimensions of ultra-racing have been largely overlooked. This study aims to identify the different types of social interactions that occur during a multi-day, ultra-race and to understand how these interactions influence ultra-runners’ race experience.MethodsAthletes competing in Britain’s “Spine Race” were recruited for the current study. Twelve male runners aged between 32 and 66 years (M = 50; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Athletes identified four considerations that contributed to changes in their training regimes: (a) social interactions; (b) inability to enact typical training routines; (c) structure and type of training; and (d) a search for new forms of well-being. Past research has demonstrated that in times of adversity, endurance athletes form ad hoc groups to support their individual goals during races ( Harman et al, 2019 ). However, the current found little evidence that athletes support each other when they migrate to online training environments.…”
Section: Discussionmentioning
confidence: 99%
“…Athletes identified four considerations that contributed to changes in their training regimes: (a) social interactions; (b) inability to enact typical training routines; (c) structure and type of training; and (d) a search for new forms of well-being. Past research has demonstrated that in times of adversity, endurance athletes form ad hoc groups to support their individual goals during races ( Harman et al, 2019 ). However, the current found little evidence that athletes support each other when they migrate to online training environments.…”
Section: Discussionmentioning
confidence: 99%
“…Runners identi ed the four categories of people they have social interactions with during the race: fellow racers, race o cials, family/friends/followers, and the general public. In a study with participants from an ultra-race, it was found that the most bene cial motivation for ultra-runners can come from a coalition of their families, friends, and followers, from their teammates, and the general public [7].…”
Section: Motivationmentioning
confidence: 99%
“…Direct support is contact with the family member, whether through a phone call or other means. However, indirect in uence from family, friends, and followers can be harmful to the runners' race-time motivation levels, as some racers noted that their loved ones can actually make them feel the physical and emotional toll of running more and would instead strictly regulate or eliminate all communication during the race [7,10]. The online presence of loved ones can emotionally encourage and support the runner, but it can also increase the pressure and nerves of runners and other athletes [7,27].…”
Section: Motivationmentioning
confidence: 99%
“…It was further explained that the child would be more confident in communicating openly in the community. Harman et al, (2019) social interactions and interpersonal relationships between individuals are affected by several things, including family, besides family, seeing the development of a very advanced era. This can be seen how an athlete who is active and not in the use of social media when in the community.…”
Section: Graph 3 Bar Chart Of Family and Social Media Categories Of Social Interactionmentioning
confidence: 99%